Algorithm for Managing Patients Hospitalized in the Surgical Wards Due to COVID-19-Related Acute Abdominal Pathology - D. G. Buribayev; D. B. Tulyaganov; Kh. E. Anvarov (Неотложная медицинская помощь)
AIM OF THE STUDY. Was to improve the outcomes of treatment of patients with COVID-19-related acute abdominal pathology by developing and implementing an algorithm for the diagnosis and treatment of those patients.MATERIAL AND METHODS. The study involved 200 patients who were randomized into two groups. This research was retrospective, based on the analysis of the medical histories of patients hospitalized with clinical manifestations of acute abdominal pathology that developed against the background of COVID-19. All medical histories in emergency departments and centers of the Republic of Uzbekistan were analyzed in the period from the beginning of the declaration of the pandemic (March 2020) to July 2022 inclusive.RESULTS. In the context of an infectious disease pandemic (COVID–19 as an example), it is very important to develop an algorithm for managing patients with acute surgical pathology. This algorithm should include a diagnostic component with the purpose of timely diagnosis of acute surgical pathology and hospitalization in the surgical department. The next step is to identify patients with a high risk of perioperative complications and adverse outcomes. The final component of the algorithm is the correction of possible risk factors for adverse outcomes.CONCLUSION. The duration of hospitalization of patients who underwent surgery for acute abdominal pathology was significantly longer during the pandemic compared to that of in the post-pandemic period (10.35±7.01 vs. 5.83±3.85 days, p<0.001), which may be due to both changes in the structure of the pathology and a larger number of complicated forms. The application of the developed algorithm will optimize the management of patients with COVID-19-related acute surgical pathology, guarantee rapid decision-making while minimizing the risk of infection, reduce the risk of complications and adverse outcomes.